2009
DOI: 10.1007/s00484-009-0257-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and oxidative stress responses of sojourners at high altitude in different climatic temperatures

Abstract: High altitude (HA) is a multi-stressor environment comprising hypobaric hypoxia and cold. Climatic temperature varies with seasonal variation at HA. The present study was undertaken to investigate the effect of ambient temperature on antioxidant profile among sojourners at HA. The study was conducted on sojourners exposed to an altitude of 4,560 m in two different seasons and categorized into two groups (SOJ 1, n=63, ambient temp. at HA: -6 degree to +10degreeC; SOJ 2, n=81, ambient temp. at HA: 3degree-22degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…However, there was not a parallel increase in the TAS. When there is greater oxidative stress due to altered metabolic rate, antioxidant processes cannot keep up with the cumulative stresses, lagging behind in serum and tissue concentrations even when antioxidant capacity is increased before exposure to high altitudes ( 23 ). Pialoux and other groups focused on antioxidant levels in sportspeople reported that free radicals increased in sportspeople at high altitudes, whereas there was not a parallel increase in the antioxidant system, similar to our fi ndings ( 14 , 20 ).…”
Section: Discussionsupporting
confidence: 88%
“…However, there was not a parallel increase in the TAS. When there is greater oxidative stress due to altered metabolic rate, antioxidant processes cannot keep up with the cumulative stresses, lagging behind in serum and tissue concentrations even when antioxidant capacity is increased before exposure to high altitudes ( 23 ). Pialoux and other groups focused on antioxidant levels in sportspeople reported that free radicals increased in sportspeople at high altitudes, whereas there was not a parallel increase in the antioxidant system, similar to our fi ndings ( 14 , 20 ).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the characteristics (gender, age, alcohol consumption, smoking, tea drinking, and BMI) of the study participants in the 2 areas were different. Environmental and physical factors, such as altitude, air quality (Jiangzha hot springs are located at high altitudes, indicating good air quality, whereas Pingshan hot springs are located at low altitudes and often exposed to hazy weather), [33][34][35] and antioxidant vitamin supplements, may have also affected the residents' condition (in Jiangzha RHSA and CA, residents often eat Hippophae rhamnoides products). 36 The impact factors and related mechanisms still need to be further studied and verified.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative damage occurring as a consequence of exposure to cold occurs as a side effect of increased thermogenesis (Venditti et al 2009) and is also associated with ischemia (Proctor 2008), but uric acid has antioxidative capacity (Álvarez-Lario and Macarrón-Vicente 2011) and there are indications of physiological increases in body uric acid levels in response to exposure to cold, including in humans (Hawkins and Zipkin 1964). Associations have been made between increased blood levels of uric acid and high altitudes in several species including cattle (Ramirez et al 1992) which were attributed at the time to hypoxia or diet, but those studies were not controlled for temperature, yet a significant and substantial contribution by cold at high altitudes has been demonstrated (Sinha et al 2010). Further, it has been suggested that high blood uric acid concentrations is an adaptation by llamas to protect against the oxidative damage associated with high altitude cold (Bakker et al 1996).…”
Section: Discussionmentioning
confidence: 99%